Maintaining Agriculture's Public Image: An Opinion Survey of Agricultural Communications Leaders - Francis S. Zaworski Jr. (Journal of Applied Communications, 1980)
Most officers of professional agricultural communications organizations believe their organizations have a responsibility to promote favorable public attitudes toward agriculture. That is one result from a recent survey of the leaders of eight of these organizations.